Comparison of physical work load in four gari frying working postures in Nigeria - Samuel, T.M.; Igbeka, J.C.; Kolawole, P. (2008)
All physical labour requires physical exertion which indicates the level of physical workload involved. This paper examines the energy expenditure in four working postures of gari-frying (garification) workers in southwestern Nigeria. The postures include sitting-beside (SB), sitting-in-front (SF), alternating-sitting-and-standing (ASS) and standing (S). Some anthropometric data, blood pressure and heart rate, were collected from 120 processors at the beginning and close of work. Physical workload was then computed using Mean Arterial Pressure (MAP), Rate Pressure Product (RPP) and Barach Energy Index (BEI). The mean total energy expenditure (TEE) for the postures was SB 3.58, SF 3.56, S 3.55, ASS 3.53 MJ8hr-day. Statistical analysis of the physical workload showed significant difference (P≤0.05) between the postures with ASS and SB consistently maintaining the lowest and highest values respectively in all the indicators. Normal range of BEI was maintained throughout the gari frying task, indicating that the task is a light one. Comparison showed that S posture had the highest myocardial oxygen consumption. Processors in sitting posture had low circulatory blood pressure while it was higher for those in standing posture, particularly ASS. ASS posture by comparison, therefore, is the best posture with least energy expenditure and is recommended for adoption.